(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article analyzes the interaction between human behavior and culture from a philosophical perspective. The study shows that social norms and values serve as primary factors regulating individual behavior, while active individual behavior contributes to the renewal and development of culture. For example, individuals who prioritize values such as respect, cooperation, and responsibility align their actions with these principles, thereby facilitating the organic and stable formation of culture. Moreover, modern technologies and global lifestyles accelerate and expand the interaction between culture and behavior. The study demonstrates that a philosophical approach allows for a deeper understanding of the dynamic relationship between behavior and culture. This article provides a theoretical and practical foundation for analyzing processes of social and cultural development.